ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 KELAS V SEMESTER I SDN 34 PONTIANAK KOTA - Rini Aprianti Fadilah; Siti Halidjah; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the 2013 curriculum lesson plans for class V SemesterI at SDN 34 Pontianak City. Analyzing the alignment of the content descriptionfor each component of the 2013 Curriculum RPP based on Permendikbudnumber 22 of 2016 and the suitability of the components seen from the principlesof preparing RPP based on Permendikbud number 14 of 2019. This type ofresearch is qualitative research, descriptive research methods. The subject of theresearch is teacher learning tools prepared by the fifth grade teacher at SDN 34Pontianak City. The data collection procedure used is indirect observation with adata collection tool in the form of an observation sheet. The results of the studyshow the alignment of the elaboration of the contents of each RPP componentguided by the Minister of Education and Culture Regulation Number 22 of 2016concerning the standard process for primary and secondary education made bythe teacher, there are parts that are appropriate and not appropriate. Theconformity of the principles of the lesson plan is guided by the regulation of theMinister of Education and culture number 14 of 2019, there are teachers who areappropriate and some are not.keywords: Analysis, Learning Implementation Plan, Thematic Curriculum2013